2016
DOI: 10.1002/joc.4696
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and restructuring of gridded precipitation data over the Greater Mekong Subregion

Abstract: Precipitation measurements in the Mekong River Basin (MRB) are full of variability due to this domain's varied weather systems, climate conditions, elevation, and specific land–atmosphere interactions. This study provides an in‐depth evaluation of the differences between four gridded precipitation products [i.e. Asian Precipitation—Highly‐Resolved Observational Data Integration Towards Evaluation of Water Resources (APHRODITE), Tropical Rainfall Measuring Mission (TRMM), CPC MORPHing technique (CMORPH), and Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 34 publications
(43 reference statements)
3
26
0
Order By: Relevance
“…While the TMPA precipitation estimates outperforms the other three precipitation products with the lowest ME, which are mainly due to its poor sampling [15]. This finding is consistent with the results of Chen et al [21]. Based on the three categorical statistical indices (POD, FAR, CSI), this study shows that all the four precipitation products have the capacity of detecting the precipitation events with relative high POD and CSI.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…While the TMPA precipitation estimates outperforms the other three precipitation products with the lowest ME, which are mainly due to its poor sampling [15]. This finding is consistent with the results of Chen et al [21]. Based on the three categorical statistical indices (POD, FAR, CSI), this study shows that all the four precipitation products have the capacity of detecting the precipitation events with relative high POD and CSI.…”
Section: Discussionsupporting
confidence: 90%
“…Based on the three categorical statistical indices (POD, FAR, CSI), this study shows that all the four precipitation products have the capacity of detecting the precipitation events with relative high POD and CSI. Among the preexisting studies, these studies show that the APHRODITE has a good performance compared with TMPA, CMORPH, CRU, and ERA-Interim and CFSR [21,30,31,39]. To our best knowledge, MSWEP has been applied for the first time to the MRB, and we found that this product outperforms the APHRODITE during the period of 1951-2007.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…APHRODITE has been used in the Asia Pacific region as baseline rainfall series for drought analysis (Um et al, 2017;Sohn et al, 2012), climate model 80 assessments (Khan et al, 2018;Cruz and Sasaki, 2017), climate change impact assessments (Apurv et al, 2015;Kulkarni et al, 2013) and hydrological model setup (Lauri et al, 2014;Panday et al, 2014). Moreover, APHRODITE's relative superiority over other rainfall products, including CFSR, is well-established in several countries in the Asia Pacific region, including Saudi Arabia (El Kenawy and McCabe, 2016), Greater Mekong (Chen et al, 2017), Bhutan (Awange and Forootan, 2016), China (Yang et al, 2014;Tang et al, 2019) and many others. The better performance of APHRODITE over CFSR and other products 85 in the region suggests that rainfall statistics derived from APHRODITE data could be more precise, and hence, more effective in generating relatively accurate synthetic weather data and better flow simulations using SWAT in rainfall dominant basins of Asia.…”
mentioning
confidence: 99%